Joey Pigza loses control - Gantos, Jack. (New York : Scholastic, 2001)
Joey, who is still taking medication to keep him from getting too wired, goes to spend the summer with the hard-drinking father he has never known and tries to help the baseball team he coaches win the championship.
Sequel to: Joey Pigza swallowed the key.
Keywords: Attention-deficit hyperactivity disorder -- Fiction; Fathers and sons -- Fiction; Baseball stories; Alcoholism -- Fiction